THE EFFECT OF PLAYING PUZZLE THERAPY ON THE FINE MOTORIC DEVELOPMENT OF PRE-SCHOOL CHILDREN IN TK TUNAS HARAPAN BATOKAN KASIMAN - Mohamad Da'i; Ira Emeilia Maulidaty (Widyagogik, 2021)
Yuniati's research (2018) at TK At Taqwa Mekarsari Cimahi found that 17 people in the puzzle intervention group found that most of the children before being given a puzzle type educational game, had moderate fine motor skills (64.7%), the rest was (35.3%) ) respondents have low fine motor development. The research objective was to determine the effect of playing puzzle therapy on fine motoric development in pre-school children at TK Tunas Harapan Batokan Kasiman in 2021. This type of research was pre-experimental with a one group pretest-posttest approach. The sample in this study were 15 children. The sampling technique used total sampling. Data collection was by means of observation on February 1, 2021. The data were analyzed univariately and bivariately using statistical test paired samples T-test. The results of the study were the mean fine motor development before being given puzzle playing therapy at TK Tunas Harapan Batokan Kasiman with a mean value of 7.87, standard deviation of 1.246. The average fine motoric development after being given puzzle playing therapy at TK Tunas Harapan Batokan Kasiman with a mean value of 9.93 standard deviation is 1.534. There is an influence on the fine motoric development of children before and after playing puzzle therapy at TK Tunas Harpan Batokan Kasiman in 2021 with a p-value (0,000). The conclusion of the research on playing puzzle therapy can affect fine motor skills in children. It is hoped that puzzle playing therapy can be applied in TK Tunas Harapan Batokan Kasiman. And it is hoped that this research can be developed with other therapies to see the fine motor development of pre-school children.